EFFECTS OF ZINC SUPPLEMENTATION ON REPRODUCTIVE PERFORMANCE IN CATTLE: A REVIEW - Syahrir Akil; Erni Damayanti; Daud Samsudewa; Ashariah Hapila; Hikmayani Iskandar (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Zinc is a vital micronutrient involved in various reproductive processes in cattle. This review aims to evaluate the effects of zinc supplementation on cattle reproductive performance by analyzing research articles sourced from Scopus and PubMed databases. Findings indicate that zinc supplementation, provided in either organic or inorganic forms, positively influences reproductive parameters. In bulls, zinc enhances sperm motility, viability, and ejaculate volume. In female cattle, supplementation modulates endocrine hormone levels during both pre-calving and post-calving periods. Moreover, appropriate zinc dosages and supplementation durations contribute to improved reproductive efficiency in cows. These results support the conclusion that zinc supplementation is effective in enhancing reproductive performance in cattle.